If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = j Solving 6 = j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-1j' to each side of the equation. 6 + -1j = j + -1j Combine like terms: j + -1j = 0 6 + -1j = 0 Add '-6' to each side of the equation. 6 + -6 + -1j = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1j = 0 + -6 -1j = 0 + -6 Combine like terms: 0 + -6 = -6 -1j = -6 Divide each side by '-1'. j = 6 Simplifying j = 6
| 9(0)-3y=-81 | | 6+3*6+6= | | 3+3*6+6= | | 0.2y=1600-8400 | | x^2-24x+27=0 | | 0.2y=8400-1600 | | 3x-24=1x+10 | | 9x-3(0)=-81 | | 8w^2+2w-1=0 | | 2+2p=6 | | 168/x=12 | | 9x-3y=-81 | | 3h^2+10h-8=0 | | n-15=31 | | 104=2v^2+8 | | x+5=4x-13 | | 12=2L+(10) | | 56=w^2+6 | | 0.25x+0.2y=350 | | 988()=1234 | | x(x+5)=-150 | | x+7=3-x | | 2y+2+10y-2=90 | | 1Dwight+2x= | | 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z | | 2(4a+5)=1.8a-3 |